Frozen Storage Characteristics of Treated and Untreated Meat from Male and Female Mussel (Perm viridis) - S.S., Sawant; S.B., Patange (Fishery Technology, 2025)
Changes in the quality of meat obtained from male and female Indian green mussel during frozen storage are reported. The usefulness of tripolyphosphate and blanching treatment in enhancing sensory quality and in retarding progression of rancidity in frozen mussels was investigated. Changes in moisture, total protein, glycogen, trimethylamine nitrogen, total volatile base nitrogen, non-protein nitrogen, salt-soluble nitrogen, drip loss, peroxide value, total bacterial count and counts of Escherichia coli, Salmonella and faecal Streptococci in frozen meat were followed every fifteen days during storage at -18Â°C. The study showed that among the treated samples, male blanched mussel product could be frozenstored in very good condition for more than 105 days and from organoleptic point of view, it had the best shelf life. However, the quality of untreated meat was acceptable for 30 days only.